Comparison and analysis of research methods for urban heat island effect based on Landsat TM6 - Shangming Dan; Huixi Xu; Wanrong Xue; Jiayi He; Bo Dan (2010 Second IITA International Conference on Geoscience and Remote Sensing, 2010)
This paper choosed Guang'an and Nanchong in the middle of Sichuan Basin as its research subjects. Using TM6 of Landsat 5 on May 1st, 2008 to recover brightness temperature, this paper compares and analyzes five methods, including comparison of highest and lowest temperature, comparison of urban and rural average temperature, comparison of difference of highest and lowest temperature in urban and rural area, comparison of heat island area and low temperature area, and heat island area index method. It concludes: (1) "Mean-Standard Deviation" can classify the grade of temperature and avoid the difference in different time phases in a way so as to reasonably depict the space distribution of thermal fields on ground surface; (2) The heat island index method that was based on "Mean-Standard Difference Classification" has strong applicability. Comparison of urban and rural average temperature was second to it. Comparison of highest and lowest temperature is the worst.